Prevent breaking bad: A proof of concept study of rebalancing the brain's rumination circuit with real‐time fMRI functional connectivity neurofeedback. Issue 4 (10th November 2020) - Tsuchiyagaito, Aki; Misaki, Masaya; Zoubi, Obada Al; ,; Paulus, Martin; Bodurka, Jerzy
Abstract: Rumination, repetitively thinking about the causes, consequences, and one's negative affect, has been considered as an important factor of depression. The intrusion of ruminative thoughts is not easily controlled, and it may be useful to visualize one's neural activity related to rumination and to use that information to facilitate one's self‐control. Real‐time fMRI neurofeedback (rtfMRI‐nf) enables one to see and regulate the fMRI signal from their own brain. This proof‐of concept study utilized connectivity‐based rtfMRI‐nf (cnf) to normalize brain functional connectivity (FC) associated with rumination. Healthy participants were instructed to brake or decrease FC between the precuneus and the right temporoparietal junction (rTPJ), associated with high levels of rumination, while engaging in a self‐referential task. The cnf group ( n = 14) showed a linear decrease in the precuneus‐rTPJ FC across neurofeedback training (trend [112] = −0.180, 95% confidence interval [CI] −0.330 to −0.031, while the sham group ( n = 14) showed a linear increase in the target FC (trend [112] = 0.151, 95% CI 0.017 to 0.299). Although the cnf group showed a greater reduction in state‐rumination compared to the sham group after neurofeedback training ( p < .05), decoupled precuneus‐rTPJ FC did not predict attenuated state‐rumination. We did not find any significant aversive effects of rtfMRI‐nf in all study participants. These results suggest that cnf has the capacity to influence FC among precuneus and rTPJ of a ruminative brain circuit. This approach can be applied to mood and anxiety patients to determine the clinical benefits of reduction in maladaptive rumination. Abstract : Regions of interest (ROI) for the connectivity‐based rtfMRI‐nf and the neurofeedback algorithm. (a) ROIs for the connectivity‐based rtfMRI‐nf. (b) Neurofeedback algorithm and display. Red circles and arrows indicate the precuneus ROI and BOLD activities, and blue circles and arrows indicate the right temporoparietal junction (rTPJ) ROI and BOLD activities. The sidebars on the screen were updated every 2‐s with positive feedback (+1: light blue color) or no feedback (0: blank color).